Analysis of the Legal Implications for the Parties Based on the Deed of Power of Attorney to Sell Where There Is a Person Who IsB-Ed - Putri Briliantini Ananiar; Aisyah Nur Prayekti (Budapest International Research and Critics University, 2022)
There is a Decision Number 3519 K/Pdt/2017 which is an appeal against the Decision of the Banda Aceh High Court numbered 43/PDT/2017/PT. The BNA, which in essence the panel of judges in the high court ruled that the Notary as defendant II was also decided by the Panel of Judges to be responsible and to be compensated along with the other defendants for the making of a Deed of Power of Attorney to Sell based on the testimony of the pretended Person. The person pretending to be someone authorized to be an obstacle in the deed, by carrying a fake Identity Card. The purpose of this study is to analyze the Legal Implications for the Parties Based on the Deed of Power of Attorney to Sell Where There Are People who pretend, through a normative juridical approach, namely regulations based on applicable laws and regulations. The results of the study provide an explanation of the decision of Cassation Number 3519 K / Pdt / 2017 which corroborates that this Deed of Power of Attorney to Sell is null and void. Thus, the aforesaid deed of power of attorney is no longer binding on the parties therein, all the powers and rights and obligations born out of the aforementioned grant of power are considered to have never existed and are binding on the parties (the person who claimed to be Z. Ahmad Nyak Cut and defendant I). in addition, there are other legal implications for the creation of a deed of power of attorney for sale in which there is a person who pretends, then according to one of the parties to the agreement, may apply for cancellation if it is found that the incompetence of the parties to the agreement.